Systemic approach to incentive athletes in bullet shooting - Grigan, S. A.; Ryzhkin, N. V.; Korobov, I. A.; Soprunov, N. I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the most effective methods of stimulation for those involved in bullet shooting.